Examining the Effect of User Participation and User Capabilities on the Accounting Information System Performance - Surtikanti Surtikanti; Sri Dewi Anggadini; Sharifah Norzehan Syed Yusuf (International Business and Accounting Research Journal, 2021)
The performance of the accounting information system is largely unsatisfactory and not optimal for many companies that use the accounting information system in their operating systems. The purpose of this study is to examine  the effect of users participation and users capcapabilities on the accounting information systems performance. A questionnaire survey was used as the primary data collection method. The population of this study is 36 companies and the sampling technique used is a non-probcapabilities sampling. Descriptive data analysis technique is used for this study and performed using SPSS V.26. The results showed that the impact of user participation on the performance of the accounting information system, the value of intervals are good enough, but still finds some things that are not optimal, and the impact of user capacity on the performance of the accounting information system shows a moderate or reasonably good interval value, but still found some things that are not optimal, namely expertise and information system performance.